2022
DOI: 10.1016/j.jclinepi.2022.01.002
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 rapid antigen tests provide benefits for epidemic control – observations from Austrian schools

Abstract: Objective : This paper motivates and justifies the use of antigen tests for epidemic control as distinct from a diagnostic test. Study Design and Setting : We discuss the relative advantages of antigen and PCR tests, summarising evidence from both the literature as well as Austrian schools, which conducted frequent, mass rapid antigen testing during the spring of 2021. While our report on testing predates Delta, we have updated the review with recent data on viral loads… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
(77 reference statements)
2
12
0
Order By: Relevance
“…More frequent testing would then give rise to logistical challenges and increased costs and could further slow RT-PCR turnaround times, resulting in a positive-feedback loop concerning delays and exacerbating negative outcomes. Our estimate argues for the efficacy of testing every two to three days with a RA test is consistent with empirical studies that have found this frequency of testing to provide an effective tool for infection surveillance within schools 67 . Therefore, rapid turnaround times for testing are essential to the utility of a surveillance program intended to suppress the spread of disease.…”
Section: Discussionsupporting
confidence: 86%
“…More frequent testing would then give rise to logistical challenges and increased costs and could further slow RT-PCR turnaround times, resulting in a positive-feedback loop concerning delays and exacerbating negative outcomes. Our estimate argues for the efficacy of testing every two to three days with a RA test is consistent with empirical studies that have found this frequency of testing to provide an effective tool for infection surveillance within schools 67 . Therefore, rapid turnaround times for testing are essential to the utility of a surveillance program intended to suppress the spread of disease.…”
Section: Discussionsupporting
confidence: 86%
“…More frequent testing would then give rise to logistical challenges and increased costs and could further slow RT-PCR turnaround times, resulting in a positive-feedback loop concerning delays and exacerbating negative outcomes. Consistent with our estimate of testing every two to three days with a RA test, the use of rapid antigen testing two to three times a week--has been empirically validated as an effective tool for disease surveillance within schools 67 . Therefore, rapid turnaround times for testing are essential to the utility of a surveillance program intended to suppress the spread of disease.…”
Section: Discussionsupporting
confidence: 63%
“…Due to the challenges of using RT-PCR, antigen-rapid diagnostic tests (Ag-RDTs) are now utilized in several countries for epidemiological surveillance and even diagnostic purposes in symptomatic individuals [ 4 ]. An observational study in Australian schools found these tests to be a power tool in suppressing the pandemic [ 5 ]. In Africa, the low number of COVID-19 cases compared to other continents have been attributed to factors such as low testing due to the high-cost of RT-PCR [ 6 ].…”
Section: Introductionmentioning
confidence: 99%